Representation of the Marine Environment in the 1994 Novel Laut Pasang by Lillpudu (Ecocritical Study: Grag Garrard) - Damanik, Muhammad Ilham Fahreza; Kusyani, Diah; Lubis, Lailan Syafira Putri (Jurnal Riset Ilmu Pendidikan, 2025)
This research is based on the relationship between humans and the environment, the impact of pollution, and human awareness of the environment. The purpose of this research is to describe the representation of the marine environment in the novel Laut Pasang 1994 by Lillpudu, and to describe the concept of ecocriticism according to Grag Garrard. This research uses descriptive qualitative method. The data sources in this research are sentences or stories that discuss the representation of the marine environment and the concept of literary ecocriticism in the novel Laut Pasang 1994 Karya Lillpudu. The way ecocritical studies work is to understand the science of the environment, therefore the results of this study show that there are representations of the marine environment and the concept of literary ecocriticism. Based on the concepts according to Grag Garrard regarding pollution, there is 1 data explaining the scattered garbage, there are 7 data where the data are houses, fields, and hospitals, 8 data disasters where the data explain the disasters of earthquakes, strong winds, and tsunamis, 0 data wilderness, 1 data animal explaining the existence of chickens, and the earth there are 3 data describing the earth there are stars, the sky, and the sun. The practical implications of this research on ecocritical concepts in the novel Laut Pasang 1994 by Lillpudu, have an important role in building character to care about the environment and awareness of the environment and instill good traits for the environment and family